PEMANFAATAN APLIKASI SNACK VIDEO SEBAGAI MEDIA PEMBELAJARAN BAHASA INDONESIA - Rifaa Venessia; Imas Juidah; Agus Nasihin; Yayah Kurniyah (Jurnal Pendidikan Educandum, 2025)
This study aims to examine the use of the SnackVideo application as a pedagogical instrument for Indonesian language education among high school students. The research used a descriptive qualitative technique, including observation, interviews, and recording processes. The data indicate that SnackVideo might serve as an engaging, dynamic, and accessible instructional platform for students. By using its short video capabilities, instructors and students may create and share original instructional materials, such as material explanations, poetry, brief tales, and succinct dramas. SnackVideo enhances students' academic motivation by presenting knowledge in a visually captivating and entertaining format. However, the application must be used under supervision to prevent misuse and ensure its conformity with educational objectives.